Purification and characterization of a ferulic acid decarboxylase from Pseudomonas fluorescens. - Huang, Z (1994)
A ferulic acid decarboxylase enzyme which catalyzes the decarboxylation of ferulic acid to 4-hydroxy-3-methoxystyrene was purified from Pseudomonas fluorescens UI 670. The enzyme requires no cofactors and contains no prosthetic groups. Gel filtration estimated an apparent molecular mass of 40.4 (+/- 6%) kDa, whereas sodium dodecyl sulfate-polyacrylamide gel electrophoresis showed a molecular mass of 20.4 kDa, indicating that ferulic acid decarboxylase is a homodimer in solution. The purified enzyme displayed an optimum temperature range of 27 to 30 degrees C, exhibited an optimum pH of 7.3 in potassium phosphate buffer, and had a Km of 7.9 mM for ferulic acid. This enzyme also decarboxylated 4-hydroxycinnamic acid but not 2- or 3-hydroxycinnamic acid, indicating that a hydroxy group para to the carboxylic acid-containing side chain is required for the enzymatic reaction. The enzyme was inactivated by Hg2+, Cu2+, p-chloromercuribenzoic acid, and N-ethylmaleimide, suggesting that sulfhydryl groups are necessary for enzyme activity. Diethyl pyrocarbonate, a histidine-specific inhibitor, did not affect enzyme activity.